PENGEMBANGAN MEDIA INFOGRAFIS BERBASIS KECERDASAN BUATAN PADA MATERI AKHLAK DALAM PENDIDIKAN AGAMA ISLAM TINGKAT SMP - Fachrudin, Yudhi (Tarbawi: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to develop artificial intelligence-based infographic learning media on moral values, particularly honesty and trustworthiness, in Islamic Religious Education (PAI) for junior high school (SMP) students, as well as to analyze the feasibility and student response to the media produced. The research method used is Research and Development with the ADDIE model, which includes the stages of needs analysis, design, development, implementation, and evaluation. The infographic media was developed using generative AI technology to produce teaching materials that are attractive, contextual, and suitable for junior high school students. The results of the study indicate that artificial intelligence-based infographic media is considered feasible for use as PAI learning media, both in terms of material and visuals. This media is able to help students understand normative moral concepts in a more concrete and contextual manner. The conclusion of this study indicates that the development of artificial intelligence-based infographic media has the potential to become an effective learning media innovation in improving the quality of moral learning in PAI at the junior high school level.